2002
DOI: 10.1182/blood-2002-04-1058
|View full text |Cite
|
Sign up to set email alerts
|

SH2-containing inositol phosphatase (SHIP-1) transiently translocates to raft domains and modulates CD16-mediated cytotoxicity in human NK cells

Abstract: Membrane recruitment of the SH2-containing 5' inositol phosphatase 1 (SHIP-1) is responsible for the inhibitory signals that modulate phosphatidylinositol 3-kinase (PI3K)-dependent signaling pathways. Herb we have investigated the molecular mechanisms underlying SHIP-1 activation and its role in CD16-mediated cytotoxicity. We initially demonstrated that a substantial fraction of. SHIP-1-mediated 5' inositol phosphatase activity associates with CD16 zeta chain after receptor cross-linking. Moreover, CD16 stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…Importantly, at the lower effector-to-target ratios, SHIP1 À/À NK cells exhibited significantly greater ADCC activity following stimulation with IL-12. This finding is an extension of the work conducted by Galandrini et al (17) because this group did not examine the role of SHIP1 in ADCC conducted by cytokine-activated NK cells.…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…Importantly, at the lower effector-to-target ratios, SHIP1 À/À NK cells exhibited significantly greater ADCC activity following stimulation with IL-12. This finding is an extension of the work conducted by Galandrini et al (17) because this group did not examine the role of SHIP1 in ADCC conducted by cytokine-activated NK cells.…”
Section: Resultssupporting
confidence: 46%
“…In fact, both the extent and duration of Ca 2+ mobilization were enhanced in cells expressing a dominant-negative form of shc, suggesting that recruitment of SHIP1 is necessary for attenuating the activation signals associated with cytotoxicity (18). Importantly, subsequent work has shown that SHIP1 catalytic activity, and not only recruitment to FcR signaling chains, is important in regulating NK cell-mediated cytotoxicity in response to NK-sensitive and antibody-coated targets (17). NK cells overexpressing WT SHIP1 exhibited significantly reduced FcgRIIIa-mediated killing of anti-CD16 mAb-coated tumor targets compared with control cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…SHIP is recruited by engagement of the inhibitory Fc receptor in B cells and mast cells (5)(6)(7)(8) or by the engagement of FcRs (Fc RI and Fc␥RIII), cytokine [interleukin 3 (IL3), granulocyte-macrophage colony-stimulating factor (GM-CSF), and TGF␤], and growth factor (steel factor and M-CSF) receptors in myeloid cells (2,9). Once SHIP is recruited to the membrane by the signaling complexes, its enzymatic activity depletes PI(3,4,5)P 3 and prevents membrane localization of PHdomain-containing factors such as Tec kinases, Akt, and PLC␥ (10)(11)(12)(13). This inhibitory effect ultimately leads to reduced calcium influx and prevents cellular activation (14).…”
mentioning
confidence: 99%